Susceptibility status of Aedes aegypti to insecticides in Atlántico (Colombia) - MAESTRE-S., RONALD; REY-V., GABRIELA; DE LAS SALAS-A, JORGE; VERGARA-S., CONSUELO; SANTACOLOMA-V., LILIANA; GOENAGA-O., SERGIO; CARRASQUILLA-F., MARÍA CRISTINA (Revista Colombiana de Entomología, 2010)
For more than three decades, chemical insecticides have been the principal measure to control dengue fever in the department of Atlántico, Colombia. We evaluated the status of susceptibility to insecticides that are used in public health like organophosphates, organochlorates, pyrethroids and carbamates on populations of A. aegypti in the department of Atlántico. Biological assays were performed applying the standardized methodology of the Center for Disease Control and Prevention (CDC), with diagnostic doses of deltamethrin (6.25 µg/ml), lambda-cyhalothrin (6.25 µg/ml), malathion (100 µg/ml), fenitothrion (75 µg/ml), propoxur (12.5 µg/ml) and dichlorodiphenyltrichloroethane DDT (150 µg/ml) on A. aegypti mosquitoes (F2) from the municipalities of Barranquilla, Soledad (Villa Katanga and Floresta), Malambo, Puerto Colombia and Baranoa. All the evaluated populations showed susceptibility to malathion and deltamethrin, five to fenitothrion, four to propoxur and two to lambda-cyhalothrin. All of them expressed loss of susceptibility to DDT. No significant differences were found in percent mortality between populations for malathion (P = 0.15), dichlorodiphenyltrichloroethane (P = 0.54) and deltamethrin (P = 0.99), while significant differences were found for lambda-cyhalothrin (P << 0.01), propoxur (P < 0.01) and fenitothrion (P << 0.01). The application of chemical insecticides for the control of dengue fever in the department of Atlántico has generated the loss of susceptibility in populations of the mosquito vector.